Empowering Education: Exploring Teachers’ Classroom Practices in Vocational Schools - Afnibar Afnibar; Amalia Amalia; Dyla Fajhriani Nasrul; Aulia Rahmi (AT-TA'LIM, 2020)
This study aimed to reveal the condition of a child-friendly school as seen from the psychological well-being students in school. Lately there have been various harassment incidents that have befallen students and their own culprit; this is allegedly related to their discomfort at school. Interviews and observations were employed in this study. The participants which were the public high school students were recruited and determined by snowball sampling. The results showed that, generally, students experienced problems; first, psychological well-being was disrupted due to the following reasons: (1) learning environment which included incomplete classroom and extracurricular activities facilities; (2) teachers’ attribute which included attitudes toward students, show less affection, appreciation and sometimes like to force the will; and (3) inadequate teaching and learning aspects which included poor lesson plans and dense of teaching and learning material. Second, psychological well-being felt by students generally in schools is related to: (1) the atmosphere in the classroom: friendly and not grumpy teachers, fun teachers in explaining the lesson; (2) understanding and easygoing friends who are comfortable to communicate with, and (3) the atmosphere outside the classroom, friendly waiters in the canteen and a comfortable and quiet library.